An evolutionary model of international competition and growth - Carolina Castaldi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The paper attempts to interpret a few stylized facts of international economic growth by means of an open economy evolutionary model. The idea is that growth models that incorporate a richer representation of the properties and effects of technological change can give a better explanation of the differentials in the growth performance and development patterns of countries worldwide. In the proposed multi-country model, growth is endogenously generated by the R&D activities performed by firms constantly searching for technological improvements. Both innovation and imitation processes are modeled and technological diffusion involves local spillovers. Firms are selected in all markets worldwide via an evolutionary replicator equation in terms of their 'competitiveness'. The predictions of the model are studied under different regimes of technological change. The model generates persistent differentiation of levels of per capita income and growth rates across countries.
Keywords: 330; growth; technological change; trade; Wirtschaftswachstum; Internationaler Wettbewerb; Evolutionsökonomik; Technischer Fortschritt; Spillover-Effekt; Theorie